Analysis of Simultaneous Village Head Elections in Sumedang Regency 2021 - Agus Toyib; Budiman Rusli; Entang Adhy; Nina Karlina (Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of this study is to explore the transfer of power at the local level through the form of democracy in the village, with an emphasis on the description of the simultaneous Village Head Elections in the Sumedang Regency in 2021. The research in this thesis employs qualitative methodologies, with the sort of research employed descriptively in the form of words, written reports, or oral descriptions of observed behavior. Data was gathered through interviews, observation, and documentation. This study's data analysis approach included the steps of data collection, data reduction, data presentation, and data conclusion. According to the study's findings, the simultaneous village head elections in Sumedang district refer to the Sumedang Regent Number 334 of 2021 decision, which will be held on October 27, 2021, in four stages: preparation, nomination, voting, and determination. Several hurdles were discovered in simultaneously picking village chiefs, including the formation of the committee, public interest, campaign implementation, and ballot counting.